Calculating the Best Efficiency Point of a Piston Diaphragm Pump Using a Metaheuristic Algorithm - Ahmadi, Hamid (Annals of Optimization With Applications, 2025)
Piston diaphragm positive displacement pumps are widely used in various industries dealing with high-viscosity fluids, such as aluminum production. They are considered among the most effective equipment for generating extremely high pressures in abrasive liquids. However, operating these devices at their optimal performance point poses a significant challenge. In the present study, the pump's performance was simulated using input and output data to derive a functional model of the pump. Subsequently, the optimal operating point was identified using the Multi-Verse Optimization (MVO) metaheuristic algorithm. The obtained optimal point was compared with the recommended point provided in the pump's characteristic curves and theoretical information from the manufacturer's manual. The results indicate the effectiveness of the proposed model and the optimization process.